"But this is a good cancer:" Patient perceptions of endometrial cancer in Denmark. Issue 1 (1st August 2018) - Sidenius, Anne; Manderson, Lenore; Mogensen, Ole; Rudnicki, Martin; Møller, Lars Mikael Alling; Hansen, Helle Ploug
Abstract: Aims and objectives: To explore endometrial cancer patients' perceptions of the disease and the influence of favourable prognoses on their experiences. Background: Endometrial cancer is associated with favourable prognoses, which may imply that patients experience distress to a lesser extent than other cancer patients with less positive treatment outcomes. However, most people with cancer report reduced quality of life and, despite endometrial cancer being prevalent worldwide, experiences of the disease have been little explored. Design: Ethnographic fieldwork with participant observations and interviews. Methods: Observations during clinical consultations at two Danish hospitals and interviews with women with endometrial cancer ( n  = 18) over a period of 6 months. The article adheres to the COREQ guidelines for reporting qualitative research. Results: We identify how patients consider cancer in general very likely to be fatal, while clinicians in contrast characterise endometrial cancer specifically as "good" because of favourable prognoses. We employ the concept of bricolage to illustrate how bits and pieces of biomedical knowledge and statistical evidence become intertwined with patients' past experiences and subjective ways of knowing, suggesting that patients' perceptions of endometrial cancer as a disease are somewhat dynamic. Conclusions: Public stories and everyday life experiences of cancer provide a central framework for illness perceptions. As a result, patients retain the idea of a close connection between cancer and death, while also adopting the notion of endometrial cancer as "good". This influenced how women responded to treatment and care. Framing endometrial cancer as "good" is not always helpful, as the impact of a cancer diagnosis per se is rarely favourable. Relevance to clinical practice: In providing women with endometrial cancer with optimal support through diagnosis and treatment, clinicians should attend to the complexity of patients' illness understandings and be aware that assuring patients of a good prognosis not always has the expected impact.